STUDI PENINGKATAN KESEJAHTERAAN PENERIMA PKH: DENGAN KUALITAS PENDAMPINGAN, TINGKAT PENDIDIKAN DAN PERUBAHAN PERILAKU DI KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Aba Yayit Al Bustomi; Andhi Supriyadi (Media Bina Ilmiah, 2025)
Program Keluarga Harapan (PKH) intended for groups registered in family-based integrated social assistance programs. This research aims to determine the impact or effects of the quality of assistance, level of education and changes in behavior on improving the welfare of PKH beneficiaries. The research was carried out using a quantitative approach using a sample of 167 PKH beneficiaries in Bandungan District, Semarang Regency, who were selected proportionally through random sampling. The data collection method involves the use of a questionnaire, then the data is analyzed using the SPSS program for multiple linear regression. The results of the study data analysis show that (1) the quality of assistance, level of education, and changes in behavior of PKH recipients have a positive and significant effect on improving their welfare, (2) these influences also occur simultaneously.